Ego defense mechanism reflected in nicholas sparks' the last song (2009) : a psychoanalytic perspective - Zuraida, Lathifah; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S. M. Hum (2014)
This study is about ego defense mechanism of major character in The Last Song novel. The problem of the study is ego defense mechanism reflected in Nicholas Sparks' The Last Song viewed from psychoanalytic perspective. The objectives of the study are identify the structural elements and psychoanalytic perspective in The Last Song. The object of the study is Nicholas Sparks' The Last Song novel (2009). It is analyzed by using psychoanalytic perspective. This study is qualitative research. There are two sources that are needed to do this research, namely: primary data sources and sec ondary data sources. The primary data source is Nicholas Sparks' The Last Song novel (2009). The secondary data sources from other sources related the study, such as: website, dictionary, some book that support the analysis. The result of the study shows the following conclusions. Firstly, based on the structural analysis, it can be concluded that in this novel, the author communicates his message to the readers that defense mechanism was done by someone to solve the problem. Secondly, based on the psychoa nalytic perspective, it can be concluded that in this novel, the author illustrates a psychological phenomenon in which people justifies the problem by doing ego defense mechanism.